Guidelines for the preparation and dosage of medicines, instructions for their use, and methods of application according to the Hilandar Medical Codex no. 517 - Vacić Zoran (Srpski Arhiv za Celokupno Lekarstvo)
The Hilandar Medical Codex is a medieval manuscript produced in the translation and copying workshop of the Hilandar Monastery (scriptorium). It is regarded as the most significant document for studying the history of Serbian medicine. The manuscript dates back to the mid-16th century. The aim of this paper is to identify and explain the measures for quantity outlined in the Hilandar Medical Codex for medicine preparation, dosage, physician instructions, contraindications, and methods of application. The analyzed material includes the deciphered text of the Hilandar Medical Codex and its translation into contemporary Serbian. To identify the scientific names of individual remedies, references were made to Dioscorides’ De Materia Medica, Antidotarium of Nicholas of Salerno, as well as general and specialized dictionaries. The prescribed weight and volume measures for the quantities of ingredients used in medicine preparation include the aksag (about 4.55 grams or 1/6 ounces), ounce, liter, cup, drop, and “handful.” In the medication dosage instructions, the measurements, with the exception of ounces, are not precise but largely descriptive. The warnings and instructions provided to the doctor regarding the use of certain drugs included the recommended duration of use and contraindications. The means of drug application included a quill (for instillation into the eye or nose), a balloon made from a pig’s bladder (vesica urinaria) with a goose quill calamus (for flushing the ureter and administering enemas), a wick (funiculus incendiarius) for applying medicine into body cavities (such as the vagina, rectum, or nose), and a sponge (litus) for applying liquid medicines to the skin’s surface.